Secretion of fibronectin by human pancreatic stellate cells promotes chemoresistance to gemcitabine in pancreatic cancer cells - Manoj Amrutkar; Monica Aasrum; Caroline S. Verbeke; Ivar P. Gladhaug (BMC Cancer, 2019)
Abstract Background Gemcitabine remains a cornerstone in chemotherapy of pancreatic ductal adenocarcinoma (PDAC) despite suboptimal clinical effects that are partly due to the development of chemoresistance. Pancreatic stellate cells (PSCs) of the tumor stroma are known to interact with pancreatic cancer cells (PCCs) and influence the progression of PDAC through a complex network of signaling molecules that involve extracellular matrix (ECM) proteins. To understand tumor-stroma interactions regulating chemosensitivity, the role of PSC-secreted fibronectin (FN) in the development of gemcitabine resistance in PDAC was examined. Methods PSC cultures obtained from ten different human PDAC tumors were co-cultured with PCC lines (AsPC-1, BxPC-3, Capan-2, HPAF-II, MIA PaCa-2, PANC-1 and SW-1990) either directly, or indirectly via incubation with PSC-conditioned medium (PSC-CM). Gemcitabine dose response cytotoxicity was determined using MTT based cell viability assays. Protein expression was assessed by western blotting and immunofluorescence. PSC-CM secretome analysis was performed by proteomics-based LC-MS/MS, and FN content in PSC-CM was determined with ELISA. Radiolabeled gemcitabine was used to determine the capacity of PCCs to uptake the drug. Results In both direct and indirect co-culture, PSCs induced varying degrees of resistance to the cytotoxic effects of gemcitabine among all cancer cell lines examined. A variable degree of increased phosphorylation of ERK1/2 was observed across all PCC lines upon incubation with PSC-CM, while activation of AKT was not detected. Secretome analysis of PSC-CM identified 796 different proteins, including several ECM-related proteins such as FN and collagens. Soluble FN content in PSC-CM was detected in the range 175–350 ng/ml. Neither FN nor PSC-CM showed any effect on PCC uptake capacity of gemcitabine. PCCs grown on FN-coated surface displayed higher resistance to gemcitabine compared to cells grown on non-coated surface. Furthermore, a FN inhibitor, synthetic Arg-Gly-Asp-Ser (RGDS) peptide significantly inhibited PSC-CM-induced chemoresistance in PCCs via downregulation of ERK1/2 phosphorylation. Conclusions The findings of this study suggest that FN secreted by PSCs in the ECM plays a key role in the development of resistance to gemcitabine via activation of ERK1/2. FN-blocking agents added to gemcitabine-based chemotherapy might counteract chemoresistance in PDAC and provide better clinical outcomes.